Formulation and Antibacterial Evaluation of Liquid Soap Containing Pineapple Peel Extract Against Staphylococcus aureus and Streptococcus pyogenes - Eliya Mursyida; Frengki Molek Wirajaya; Olvaria Misfa (LPPM Akafarma Sunan Giri Ponorogo, 2026)
The increasing prevalence of antimicrobial resistance highlights the need for alternative antibacterial agents, particularly against Gram-positive pathogens such as Staphylococcus aureus and Streptococcus pyogenes. Pineapple peel (Ananas comosus (L.) Merr.), an agricultural by-product, contains bioactive compounds with reported antimicrobial activity. This study aimed to formulate ethanol extract of pineapple peel into a liquid soap and evaluate its physicochemical properties and antibacterial effectiveness. The extract was incorporated at concentrations of 5%, 10%, and 15%. Physicochemical evaluations included organoleptic properties, homogeneity, pH, free alkali content, and specific gravity. Antibacterial activity was determined using the agar well diffusion method against S. aureus and S. pyogenes. All formulations met general quality requirements for liquid soap preparations, with pH values ranging from 7.3 to 9.7, specific gravity between 1.01 and 1.04g/mL, and free alkali content ≤0.1%. Antibacterial testing demonstrated a concentration-dependent increase in inhibition zone diameter. The 15% formulation exhibited the highest activity, producing inhibition zones of 13.30mm against S. aureus and 20.25mm against S. pyogenes, with statistically significant differences compared to lower concentrations (p < 0.05). These findings indicate that pineapple peel extract can be successfully incorporated into a stable liquid soap formulation while retaining its antibacterial activity. The 15% formulation shows promising potential as a natural-based antibacterial cleansing product.